THE CORRELATION BETWEEN EDUCATION AND MATERNAL KNOWLEDGE ON HIV TESTING - Tina Endah Pratiwi; Meirita Herawati; Emaretha Mikaningtyas (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Backgrounds: Pregnant women with HIV will be at risk of transmitting her disease to their babies. HIV testing is an important opening gate of HIV status in pregnant women. The program manager of AIDS Prevention Commission of Bekasi Regency, Ade Buwono, revealed that from 711 HIV-infected, 53% were housewives, found 16 infants were infected with the deadly diseaseAims: In this recent study, correlation between education maternal knowledge about HIV testing was underlined. Methods: This research was a type of analytic research with cross sectional method. A total of 50 pregnant women from Independent Midwife Clinic “MARNIH HANDAYANI” was selected using accidental sampling approach. The participants were given questionnaire related to measure the knowledge level of respondents to HIV testing. Results: From the results, it is shown that the level of knowledge of pregnant women about HIV testing is still very low. This study shows knowledge to HIV examination among the respondents is defined by the education level (p value < 0.001), age (p value < 0.001) and the information source (p value < 0.001). Conclusion: The results shows the importance of the health personnel to provide HIV counseling to every visiting pregnant woman. Health care provider had to educate all pregnant women to test HIV. This is because early HIV / AIDS detection will reduce the risk of Mother-to-Child Transmission.